تطور سياسة العمران في الأندلس والعوامل المساهمة في تطورها (138- 422هـ/ 755- 1031م) - صارم وفاء (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
تتميز العمارة عن العلوم والآداب والفنون بأنها أهم المراجع وأصدقها لتجسيم مراحل التاريخ, وتطور الحضارات, وإذا كانت العلوم والآداب قد ازدهرت في الأندلس فإن العمارة تكونت عربية إسلامية بالمطلق, وهذه الصيغة لعب فيها الدور السياسي والاقتصادي والظروف الحلية, دوراً هاماً ولا نستطيع أن نفصل دور الدين عنها, لذلك نشأت مدن وتطورت, وقصور ومساجد كان لها هدف وليس فقط الجمالية, وهذا الأمر سيحاول البحث الوقوف عندها. Architecture differs from science and arts by being the most important and reliable reference in reflecting different phases of history and the development of civilizations. If science and arts have flourished in Andalusia, Architecture was formed with an absolute Islamic nature. This formula was influenced by the role played by politics, economy and the local issues. Needless to say that the role of religion can never be separated from architecture. Therefore, many cities emerged and many palaces and mosques developed. All these architectural buildings have certain goals not only aesthetic. This issue is to be addressed and discussed in this research.